ANALYSIS OF MECHANICAL STRENGTH OF KEVLAR, CARBON, AND GLASS FIBER POSITIONS REINFORCED WITH EPOXY RESIN FOR FIBERGLASS SHIP HULL ZONES - Khanissa Alfita Santoso Putri (Applied Science and Technology on Naval Engineering, 2026)
The use of fiber-reinforced polymer (FRP) composite materials has become a primary solution in modern ship hull construction to reduce structural weight without compromising strength. This study aims to analyze the mechanical strength characteristics of hybrid composite materials reinforced with Kevlar, carbon, and glass fibers using an epoxy resin matrix, with particular emphasis on various stacking sequence configurations. The main focus of the research is to evaluate the effect of fiber stacking order on tensile strength, yield strength, and elastic modulus. Mechanical performance was assessed through tensile testing conducted in accordance with ISO 527-4, a standard specifically intended for determining the tensile properties of unidirectional fiber-reinforced composites. Test specimens were fabricated using the hand lay-up method, with fibers uniformly oriented at a 0° direction. The results indicate that the stacking sequence configuration has a significant influence on mechanical performance. The placement of carbon fiber, which possesses a very high elastic modulus (up to 400 GPa), contributes substantially to the overall stiffness of the composite. Meanwhile, Kevlar fiber, with its high failure strain (approximately 14%), enhances the material’s energy absorption capability. This analysis provides technical recommendations for optimal fiber layer configurations, particularly for ship hull zones that require high structural strength and durability under marine environmental conditions.